Media use and agricultural productivity: Qualitative study of Yemen agroforestry smallholder farmers - Saeed, Ali Abdullah Mohammed; Abdul Rahman, Nik Adzrieman (2018)
This paper seeks to understand the extent of media use among the smallholder farmers in Yemen and how low agricultural information dissemination leads to low farming knowledge that consequently reduces productivity. The agriculture is still a critical resource in the country for combating widespread poverty and food insecurity. Farmers worldwide still prefer interpersonal communication over other sources to access agricultural information. In the context of Yemen, the paper is intended to identify sources and mediums the smallholder farmers favor to use, farming topics needed to improve their output and constraints that hinder them from accessing effective farming practices. A qualitative design is proposed to conduct the study through employing a semi structured interview to elicit the data from 30 agroforestry smallholders who would be selected purposively in coordination with the Ministry of Agriculture. The agroforestry farmers were chosen because agroforestry is the most common farming in the populous north Yemen.